2016
DOI: 10.1590/1983-084x/15_192
|View full text |Cite
|
Sign up to set email alerts
|

Óleos essenciais e vegetais no controle in vitro de Colletotrichum gloeosporioides

Abstract: RESUMO:O objetivo deste trabalho foi avaliar a atividade antifúngica de óleos essenciais e vegetais no controle in vitro de Colletotrichum gloeosporioides, agente causal da antracnose em pós-colheita de frutíferas. Treze óleos essenciais foram utilizados em concentrações de 0,00%, 0,40%, 0,80%, 1,70%, 3,20%, 6,25%, 12,50%, 25,00%, 50,00% e 100,00%, e uma linhagem padrão de Colletotrichum gloeosporioides. Foram avaliadas a concentração inibitória mínima e a concentração mínima fungicida a fim de caracterizar o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
6
0
7
Order By: Relevance
“…The essential oils of all species of medicinal plants evaluated, with the exception of saffron, were 100% effective at all concentrations against all fungi. Ramos et al [5], found similar results in a study where the total inhibition of the mycelial growth of C. gloeosporioides by the essential oils of C. citratus and C. citriodora was observed in the concentrations of 6.25% and 3.2%, respectively. The antifungal activity of citral, the major constituent of the essential oil of C. citratus, may cause rupture of the cell membrane integrity and extravasation of the cellular components of the microorganisms.…”
Section: Antifungal Activity Of Essential Oilssupporting
confidence: 63%
See 1 more Smart Citation
“…The essential oils of all species of medicinal plants evaluated, with the exception of saffron, were 100% effective at all concentrations against all fungi. Ramos et al [5], found similar results in a study where the total inhibition of the mycelial growth of C. gloeosporioides by the essential oils of C. citratus and C. citriodora was observed in the concentrations of 6.25% and 3.2%, respectively. The antifungal activity of citral, the major constituent of the essential oil of C. citratus, may cause rupture of the cell membrane integrity and extravasation of the cellular components of the microorganisms.…”
Section: Antifungal Activity Of Essential Oilssupporting
confidence: 63%
“…For the study and validation of these alternative methods, researches have been carried out in vitro to assess the potential of medicinal plants for the control of phytopathogenic fungi using essential oils and aqueous extracts [4,5]. In addition, researches in vivo have been developed in order to verify the resistanceinducing activity of such products.…”
Section: Introductionmentioning
confidence: 99%
“…Andrade e Vieira (2016) efeito sobre a germinação de conídios, in vitro e in vivo. Ramos et al (2016) observaram que o óleo essencial de cravo da índia na concentração de 6,25% foi eficiente no controle de Colletotichum gloesporioides, ainda ressaltaram que para um efeito satisfatório é necessário empregar uma concentração adequada a cada microrganismo. Resultados similares ao encontrado por Fialhio et al 2015que determinaram o efeito fungicida do óleo essencial de canela a campo na redução da severidade de Phakopsora euvitis.…”
Section: Resultsunclassified
“…A decrease in the growth rate was observed with oil concentration increased until the growth of phytopathogens was stopped when submitted to their respective MICobs (See Table 1), there was a significant difference in the negative controls that showed the highest growth According to literature, the phenolic compound Eugenol is the major constituent of clove essential oil, in addition to other chemical compounds such as β-caryophyllene, αhumulene, caryophyllene oxide and eugenyl acetate in lower concentrations [21,22,34,35]. The fungitoxicity of eugenol and other compounds has been reported in some studies [26,35,36,37]. The mechanism of action of clove essential oil is associated with its hydrophobicity, which provides interaction with the wall and lipids of the cell membrane and mitochondria, altering cellular permeability and causing disturbances in its structures.…”
Section: Means Of the Index Of Mycelial Growth Speed (Cm Day -1 ± Sd)mentioning
confidence: 98%